Pengaruh Learning Cycle–5E Berkonteks SSI Terhadap Pemahaman Hakikat Sains Pada Materi Larutan Penyangga Dan Hidrolisis Garam Siswa SMA - Eris Ratnawati; Sri Rahayu; Fauziatul Fajaroh (Jurnal Pendidikan Sains, 2016)
Abstract: The aims of this study were to investigate the difference of students' nature of science understanding who were taught using 5E learning cycle model with SSI learning context and conventional model on buffer solution and salt hydrolysis. This study used quasi-experimental with pretest and post-test design. The sample considered two classes and selected by convenience sampling technique in SMAN Tulungagung. The data were obtained using the questionnaires nature of science Likert scale (R = 0.883) and analyzed by one way ANCOVA and effect size. The research results showed significant different on students’ nature of science understanding between students who were taught using 5E learning cycle model with SSI learning context and students who taught using conventional model. Based on effect size, nature of science aspects that large contribute was the scientific method, empirical, inference, social dimension of science, and Social and cultural embeddedness of science. Aspects of the nature of science that medium contributes was tentative, creative, and theory driven. While the theory and law were small contribute.Key words: Learning Cycle-5E , Socioscientific Issues, Nature Of Science, Buffer Solution, Salt Hydrolysis Abstrak: Penelitian ini bertujuan menguji perbedaan pemahaman hakikat sains siswa yang dibelajarkan dengan model pembelajaran Learning Cycle-5E berkonteks SSI dan model pembelajaran konvensional pada materi larutan penyangga dan hidrolisis garam. Penelitian ini menggunakan rancangan penelitian eksperimen semu dengan pretes dan pascates. Sampel terdiri dari dua kelas dan dipilih menggunakan teknik convenience sampling di SMAN Tulungagung. Data diperoleh menggunakan instrumen angket hakikat sains berskala likert (R = 0,883) dan dianalisis dengan ANCOVA satu jalur dan effect size. Hasil penelitian menunjukkan ada perbedaan signifikan pemahaman hakikat sains siswa yang dibelajarkan dengan model pembelajaran Learning Cycle-5E berkonteks SSI dan model pembelajaran konvensional. Berdasarkan effect size, aspek hakikat sains yang berkontribusi tinggi adalah metode ilmiah, empiris, inferensi, dimensi sosial sains, dan penerapan sains dalam bidang sosbud. Aspek hakikat sains yang berkontribusi sedang adalah tentatif, kreatif, dan theory driven. Sedangkan hukum dan teori berkontribusi kecil.Kata kunci: Learning Cycle-5E , Socioscientific Issues, Hakikat Sains, Larutan Penyangga, Hidrolisis Garam